- Factorise:
(i) 5x^{2} – 20xy
Solution:
= 5x(x – 4y)
(ii) 2p(x + y) – 3q(x + y)
Solution:
= (x + y) (2p – 3q)
(iii) 4(a + b)^{2} – 6(a + b)
Solution:
= 2 (a + b) [2(a + b) – 3]
= 2 (a + b) (2a + 2b – 3)
(iv) 18x^{2}y – 24xyz
Solution:
= 6xy (3x – 4z)
(v) 7xa – 70 xb
Solution:
= 7x (a – 10b)
(vi) 13m^{2} + 156n^{2}
Solution:
=13(m^{2} + 12n^{2})
(vii) 3x^{2} + 6x +6
Solution:
= 3 (x^{2} + 2x + 2)
(viii) 4abx^{2} + 8abx + 120by
Solution:
= 4ab (x^{2} + 2x +3y)
- Factorise
(i) x^{2} + xy + xz + yz
Solution:
= x (x + y) + z (x+ y)
=(x + y) (x + z)
(ii) a^{2} – ab + ac – bx
Solution:
= a (a – b) + c (a – b)
= (a – b) (a – c)
(iii) 4x + bx + 4b + b^{2}
Solution:
= x (4 + b) + b (4 + b)
= (4 + b) (x + b)
(iv) 6ax – 6a + 5a – 5
Solution:
= 6a (x – 1) + 5 (x – 1)
= (3x + 5) (x^{2} + 1)
(v) a^{3} + a^{2}b + ab + b^{2}
Solution:
= a^{2} (a +b) + b (a +b)
= (a + b) (a^{2} + b)
(vi) 3x^{3} + 5x^{2 }+ 3x +5
Solution:
= x^{2} (3x +5) + 1 (3x + 5)
= (3x + 5) (x^{2} + 1)
(vii) y^{4} – 2y^{3} + y – 2
Solution:
= y^{3}(y – 2) + 1 (y – 2)
= (y – 2) (y^{3} – 1)
= (y – 2) (y^{3} – 1^{3})
= (y – 2) (y + 1) (y^{2} – y +1)
(viii) t^{4} + t^{4} – 2t – 2
Solution:
= t^{3} (t + 1) – 2(t +1)
= (t – 1) (t^{3} – 2)
5x(x – 4y) = 5×2 – 20xy [ not 5×2 – 2xy]
oh oh that might be typing mistake . Thank you for reminding 🙂